2019
DOI: 10.1038/s41434-019-0081-8
|View full text |Cite
|
Sign up to set email alerts
|

Bat adeno-associated viruses as gene therapy vectors with the potential to evade human neutralizing antibodies

Abstract: The prevalence of adeno-associated virus (AAV) has been investigated in bat populations, but little is known about the biological properties of this virus. In this study, four full-length bat AAV capsid genes were isolated in China, with their amino acid sequences sharing 61% identity with those of AAV2 on average. These capsid genes could package AAV particles in combination with AAV2 rep and ITRs, albeit at a lower efficiency. Bat AAVs could only slightly infect mouse liver but could transduce mouse muscle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Analysis of the BtAAV capsid structure using sequence analysis and cryo-EM revealed unique structural differences to human AAVs, including insertions and deletions in the capsid surface loops [ 221 ]. BtAAV capsids have been identified as possible vectors for gene therapy, as discussed later [ 221 , 222 ].…”
Section: Genus Dependoparvovirusmentioning
confidence: 99%
“…Analysis of the BtAAV capsid structure using sequence analysis and cryo-EM revealed unique structural differences to human AAVs, including insertions and deletions in the capsid surface loops [ 221 ]. BtAAV capsids have been identified as possible vectors for gene therapy, as discussed later [ 221 , 222 ].…”
Section: Genus Dependoparvovirusmentioning
confidence: 99%
“…Bats are a rich source of AAV genetic diversity [ 68 , 69 ] and may provide capsids with improved tropism and immune evasion properties. For example, bat AAV sequences have low capsid sequence identity (<60%), reduced antibody neutralization profiles, and increased muscle to liver transduction ratios compared to primate AAVs [ 70 ]. Bat AAV10HB was chosen for additional structural studies, and divergent loop structures were observed between AAV2, AAV5, and AAV10HB.…”
Section: Aav Capsid Modification Strategiesmentioning
confidence: 99%
“…For example, synthetic variants obtained by structure-guided antigenic epitope evolution allows evading neutralizing antibodies (NAbs) [154]. Using an AAV capsid from other host species may also hide the virus from the pre-existing NAbs [155]. Empty capsids can act as bait for antibodies, promoting the distribution of the target vector [156].…”
Section: Viral Vectorsmentioning
confidence: 99%